2015
DOI: 10.1021/acs.est.5b00558
|View full text |Cite
|
Sign up to set email alerts
|

Bioconcentration and Transfer of the Organophorous Flame Retardant 1,3-Dichloro-2-propyl Phosphate Causes Thyroid Endocrine Disruption and Developmental Neurotoxicity in Zebrafish Larvae

Abstract: 31Organophosphate flame retardants are emerging environmental contaminants, 32 although knowledge of their health risks is limited. Here, thyroid hormone 33 homeostasis and neuronal development was studied in the progeny of adult zebrafish 34 exposed to tris (1, 3-dichloro-2-propyl) phosphate (TDCPP). Adult zebrafish were 35 exposed to TDCPP (0, 4, 20, and 100 µg/L) for 3 months. Increased generation of 36 reactive oxygen species and reduced survival rates was observed in exposed F1 larvae. 37We also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(90 citation statements)
references
References 62 publications
9
81
0
Order By: Relevance
“…The supernatants were stored at Ϫ20°C, and the protein concentration was measured by using a bicinchoninic acid (BCA) protein assay kit (Beyotime Institute of Biotechnology, Nanjing, China). Western blot analysis was performed according to previously described methods (22,23). Proteins (50 mg/sample) were transferred to polyvinylidene difluoride (PVDF) membranes.…”
Section: Figmentioning
confidence: 99%
“…The supernatants were stored at Ϫ20°C, and the protein concentration was measured by using a bicinchoninic acid (BCA) protein assay kit (Beyotime Institute of Biotechnology, Nanjing, China). Western blot analysis was performed according to previously described methods (22,23). Proteins (50 mg/sample) were transferred to polyvinylidene difluoride (PVDF) membranes.…”
Section: Figmentioning
confidence: 99%
“…Moreover, the results of numerous animal experiments have indicated the disruptive effect of OPEs on the thyroid endocrine system. Wang et al (2013Wang et al ( , 2015aWang et al ( , 2015b found that TDCPP changed TH levels and altered the transcription of genes involved in the hypothalamic-pituitary-thyroid (HPT) axis in zebrafish embryos/larvae. Liu et al (2013a) evaluated the effects of TDCPP and TPP on six receptor-associated expression of mRNA in zebrafish embryos/ larvae, and the results showed that TH receptor-centered gene networks were altered by OPEs.…”
Section: J O U R N a L O F E N V I R O N M E N T A L S C I E N C E Smentioning
confidence: 99%
“…Toxicology studies have shown that exposure to OPEs has the potential to cause developmental toxicity (McGee et al, 2012), neurotoxicity (Wang et al, 2015a(Wang et al, , 2015b, adverse reproductive (Liu et al, 2013b), disruption to the endocrine system (Liu et al, 2012) and a range of other systemic effects in experimental animal models (Dishaw et al, 2014). However, knowledge of the toxicological mechanisms of OPEs remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…Published data suggest that exposure to TDCIPP causes various toxicities depending on organisms tested, such as endocrine disruption (Kojima et al, 2013;Liu et al, 2013;Zhang et al, 2014;Wang et al, 2015a), neural toxicity (Dishaw et al, 2011(Dishaw et al, , 2014Ta et al, 2014;Wang et al, 2015bWang et al, , 2015c, hepatoxicology (Crump et al, 2012;Farhat et al, 2013Farhat et al, , 2014aFarhat et al, , 2014bLiu et al, 2016) and developmental and reproductive toxicity (Liu et al, 2012;Liu et al, 2013;McGee et al, 2012;Farhat et al, 2013;Fu et al, 2013;Wang et al, 2015a). For example, acute exposure to TDCIPP affects embryonic development by delaying remethylation of the zygotic genome and embryonic epiboly and results in significantly greater mortality in embryos of zebrafish (McGee et al, 2012;Fu et al, 2013).…”
mentioning
confidence: 99%
“…Using the model aquatic organism and ciliated protozoa T. thermophila, it has been found that acute exposure to TDCIPP decreases biomass by reducing number of cells, size of cells and quantity of cilia (Li et al, 2015b). Furthermore, two studies have reported that chronic exposure to relatively small concentrations of TDCIPP resulted in bioconcentration of the chemical, which resulted in adverse effects on reproduction and developmental of F 0 zebrafish (Wang et al, 2015b(Wang et al, , 2015c; TDCIPP was also detected in F 1 eggs following parental exposure, causing developmental neurotoxicity in F 1 larvae of zebrafish (Wang et al, 2015b). Recently, effects of TDCIPP on development have been evaluated in zebrafish and the water flea (Crustacea; Daphnia magna) exposed to environmentally relevant concentrations (Li et al, 2015a;Zhu et al, 2015).…”
mentioning
confidence: 99%